Characterization of DMS Zn1-xAxO (A: Fe, Ni, Co and Mn, x: 0.01, 0.02, …, 0.1) grown by ECD method. (June 2016) - Güney, Harun; Coşkun, Cevdet; Meral, Kadem; Tatar, Demet
Abstract: Zn1-x Ax O (A: Fe, Ni, Co and Mn, x: 0.01, 0.02, …, 0.1) films, grown by electrochemical deposition (ECD) on indium tin oxide (ITO) substrate, was characterized by structural, optical, electrical and magnetic techniques. Energy-Dispersive-X-Ray-Fluorescence (EDXRF) spectroscopy showed 5% dopants A. X-ray diffraction (XRD) measurements clearly showed formation of all Zn0, 95 A0, 05 O thin films with a strong c-axis (002) preferential orientation. It was calculated a hexagonal wurtzite structure with XRD results. Absorption measurements of the samples were taken about and an important variation in these measurements were not detected as depend on percentage changes of dopant A. Photoluminescence (PL) measurements showed that PL intensities increase in n -type materials, decrease in p -type materials depending upon increasing doping rate of the grown films. Atomic force microscopy (AFM) pictures of films shows that the most homogeny film is Zn0, 95 Co0, 05 O and the most roughness film Zn0, 95 Mn0, 05 O. Hall measurements showed that samples doped 5% Fe and Co within ZnO are n -type and other samples doped 5% Ni and Mn within ZnO are p -type. Magnetoresistance (MR) measurements show that all films have feature diluted magnetic semiconductor (DMS) at room temperature. Highlights: A doped ZnO by ECD shows DMS property at room temperature. Fe and Co doping ZnO films were shown n-type conductivity. Ni and Mn doping films were shown p-type conductivity. PL intensities increase in n-type, decrease in p-type by increasing doping rate.